2023
DOI: 10.1186/s40798-023-00573-9
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Promotes Tissue Regeneration: Mechanisms Involved and Therapeutic Scope

Abstract: Exercise has well-recognized beneficial effects on the whole body. Previous studies suggest that exercise could promote tissue regeneration and repair in various organs. In this review, we have summarized the major effects of exercise on tissue regeneration primarily mediated by stem cells and progenitor cells in skeletal muscle, nervous system, and vascular system. The protective function of exercise-induced stem cell activation under pathological conditions and aging in different organs have also been discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 138 publications
(170 reference statements)
0
4
0
Order By: Relevance
“…Considering that DDAH1 is beneficial for muscle regeneration, the upregulation of DDAH1 might be a self-protective mechanism in response to CTX. Interestingly, exercise training is believed to promote muscle regeneration after injuries [ 48 ]. We previously observed that swimming for 8 weeks increases myocardial DDAH1 expression and promotes cardiac angiogenesis in mice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that DDAH1 is beneficial for muscle regeneration, the upregulation of DDAH1 might be a self-protective mechanism in response to CTX. Interestingly, exercise training is believed to promote muscle regeneration after injuries [ 48 ]. We previously observed that swimming for 8 weeks increases myocardial DDAH1 expression and promotes cardiac angiogenesis in mice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The practice of physical activity, endogenous metabolites, and dietary nutrients can directly influence epigenetic enzymes. Epigenetic modifications to DNA and histone proteins alter cell fate by controlling chromatin accessibility and downstream gene expression patterns [18].…”
Section: Gut Microbiota Nutrients and Muscle Performancementioning
confidence: 99%
“…These metabolites can serve as activators or inhibitors of epigenetic writers, such as Jumonji C domain-containing proteins (JmjC), DNA methyltransferases (DNMTs), histone acetyltransferases (HATs), ten-eleven DNA translocase demethylases (TETs), and histone deacetylases (HDACs). In this sense, metabolites can influence nutrient-sensing signaling pathways [18,19].…”
Section: Gut Microbiota Nutrients and Muscle Performancementioning
confidence: 99%
See 1 more Smart Citation